THE IMPACT OF NEUROSCIENCE-BASED MINDFULNESS TRAINING ON MENTAL HEALTH IN FUTURE PSYCHOLOGISTS - Olha Lazorko (Психологічні перспективи)
Purpose. This study investigates the effectiveness of a neuroscience-based mindfulness training program on emotional states, self-compassion traits and well-being status among psychology students during an 8-week intervention. The work focuses on developing emotional regulation, decreasing stress and depression, and increasing self-compassion and mindfulness — all of which are crucial skills for professional practice.